In vitro antibacterial activity of imipenem in combination with colistin against multi-drug resistant ACINETOBACTER BAUMANNII - Sakulthip Panapakdee (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007